The role of neighborhood inequalities on diabetes prevention care: a mini-review - Frigerio, Francesco; Muzzioli, Luca; Pinto, Alessandro; Donini, Lorenzo Maria; Poggiogalle, Eleonora (Frontiers in Clinical Diabetes and Healthcare, 2023)
Diabetes is one of the most prevalent non-communicable diseases in modern society. A recently emergedA research niche has emerged focused during the last years, investigatingon social determinants of health in relation with diabetes mellitusthe link between social determinants of health and diabetes mellitus, one of the most prevalent non-communicable diseases in modern society.. The aim of the present narrative mini-review is to explore and summarize current findings in this field targeting high-income countries. In the presence of disadvantaged neighborhood factors (including socioeconomic status, food environment, walkability, and neighborhood aesthetics), diabetes prevention and care are affected at a multidimensional level. The vast majority of the included studies suggest that, besides individual risk factors, aggregated neighborhood inequalities should be tackled to implement effective evidence-based policies for diabetes mellitus.